Alzheimer’s disease: the role of extrinsic factors in its development, an investigation of the environmental enigma - Suresh, Swathi; Singh S, Ankul; Rushendran, Rapuru; Vellapandian, Chitra; Prajapati, Bhupendra (Frontiers in Neurology, 2023)
In the realm of Alzheimer's disease, the most prevalent form of dementia, the impact of environmental factors has ignited intense curiosity due to its substantial burden on global health. Recent investigations have unveiled these environmental factors as key contributors, shedding new light on their profound influence. Notably, emerging evidence highlights the detrimental role of various environmental contaminants in the incidence and progression of Alzheimer's disease. These contaminants encompass a broad spectrum, including air pollutants laden with ozone, neurotoxic metals like lead, aluminium, manganese, and cadmium, pesticides with their insidious effects, and the ubiquitous presence of plastics and microplastics. By meticulously delving into the intricate web connecting environmental pollutants and this devastating neurological disorder, this comprehensive chapter takes a deep dive into their involvement as significant risk factors for Alzheimer's disease. Furthermore, it explores the underlying molecular mechanisms through which these contaminants exert their influence, aiming to unravel the complex interactions that drive the pathogenesis of the disease. Additionally, this chapter proposes potential strategies to mitigate the detrimental effects of these environmental contaminants on brain health, with the ultimate goal of restoring and preserving typical cognitive function. Through this comprehensive exploration, we aim to enhance our understanding of the multifaceted relationship between neurotoxins and Alzheimer's disease, providing a solid foundation for developing innovative in-vivo models and advancing our knowledge of the intricate pathological processes underlying this debilitating condition.